CAGAR BUDAYA SANG PENUTUR MASA SILAM CULTURAL HERITAGE THE TELLER OF THE PAST - Sutaba, I Made (Puslitjakdikbud Balitbang Kemdikbud, 2019)
Archaeological researches in Indonesia have discovered a number of various historical and archaeological artifacts that belong to cultural heritage. As historical evidences, this cultural heritage is an important source of the plural information and messages of the past life of our society. It is remarkable that this cultural heritage has some problems for example problem of typology, function, meanings, and the other for the society. Studying the problems, it is interesting to do research on its function as a teller of the past history that contained various aspects of the life of our society that not yet studied until today. By learning the problems, this research goal is to find the answer of the problems. To reach this goal, we do this research gradually by collecting data through literature study and field observation along with interviews. The next step is analysis carried out through methods of typology analysis, contextual, functional analysis, ethno archaeological and ethno historical approach. Finally the result showed that the function of our cultural heritage is as teller of the many-sided aspects of the past history of our artifacts such as technological aspects, social, and religious aspects but it is impossible to get full completed information due to some reasons. Keywords: archaeological and historical artifacts, cultural heritages, teller of the past. Â AbstrakPenyelidikan arkeologi di Indonesia sudah berhasil menemukan artefak sejarah dan arkeologi yang beraneka ragam, yang tergolong sebagai warisan budaya. Sebagai bukti-bukti sejarah, warisan budaya ini adalah sumber informasi dan pesan-pesan kehidupan masyarakat masa lalu yang bersifat pluralistik. Menarik perhatian, bahwa warisan budaya ini mempunyai permasalahan yaitu, permasalahan tipologi, fungsi dan makna dalam kehidupan masyarakat. Mempelajari masalah ini, sangat menarik untuk melakukan penelitian mengenai fungsinya sebagai penutur sejarah masa silam, yang mengandung aneka ragam, aspek kehidupan masyarakat, yang belum dikaji sampai sekarang. Dengan mencermati permasalahan ini, maka tujuan penelitian ini, adalah untuk meneliti permasalahan tadi. Untuk mencapai tujuan ini, penulis melakukan penelitian secara bertahap melalui pengumpulan data dengan metode kajian pustaka dan observasi lapangan yang disertai dengan wawancara. Langkah selanjutnya, adalah melakukan analisis dengan analisis tipologi, kontekstual, analisis fungsional, pendekatan etnoarkeologi dan etnohistori. Hasil penelitian ini menunjukkan bahwa cagar budaya itu berfungsi sebagai penutur kehidupan masa silam yang mengandung aspek yang bersfiat jamak, adalah aspek teknologi, sosial dan religi, tetapi tidak mungkin untuk mendapat informasi yang lengkap karena berbagai faktor.Kata kunci: peninggalan sejarah dan purbakala, warisan budaya, penutur masa silam.